PENGARUH PENERAPAN K3 (KESELAMATAN KERJA, KESEHATAN KERJA, KEAMANAN KERJA) DAN GAJI TERHADAP KINERJA KARYAWAN DI CV. MALALA - Lianova Lianova (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Companies in the technology sector are companies that continue to grow with the times. The company is required to play an active role in technological sophistication that can be useful for the community. Increasingly optimal employee performance can help the company to continue to grow. Employee performance can be influenced by K3 and salary factors. This research is a descriptive research with a quantitative approach. The sampling technique in this study used a saturated sample technique with a total of 45 employees. Data obtained through questionnaires or questionnaires, observations and interviews. From the results of the analysis that has been carried out, the results of the study indicate that the work safety variable (X1) partially affects employee performance (Y). Occupational health variable (X2) has no effect on employee performance (Y) partially. The job security variable (X3) has a partial effect on employee performance (Y). Salary variable (X4) partially affects employee performance (Y). K3 and salary variables have an effect on employee performance (Y) simultaneously in CV. Malala.